Peer interaction and written input: Influence of written input on the oral interactions of German as a foreign language learners - Kirchhoff, Natalie (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The present study investigated the influence of written input on oral peer interactions in a German as a foreign language classroom. Learners participated in six interactive classroom activities. One group of fourteen learners was exposed to oral input during the activities and the other group of fourteen learners, apart from oral input also received written input. Oral interactions were audio recorded and transcribed in order to analyse the frequency and nature of language-related episodes (LREs). The results suggest that written input influences oral interactions.